2016
DOI: 10.1371/journal.pone.0158529
|View full text |Cite
|
Sign up to set email alerts
|

CCL21/CCR7 Axis Contributed to CD133+ Pancreatic Cancer Stem-Like Cell Metastasis via EMT and Erk/NF-κB Pathway

Abstract: BackgroundTumor metastasis is driven by malignant cells and stromal cell components of the tumor microenvironment. Cancer stem cells (CSCs) are thought to be responsible for metastasis by altering the tumor microenvironment. Epithelial-mesenchymal transition (EMT) processes contribute to specific stages of the metastatic cascade, promoted by cytokines and chemokines secreted by stromal cell components in the tumor microenvironment. C-C chemokine receptor 7 (CCR7) interacts with its ligand, chemokine ligand 21(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 36 publications
2
40
0
Order By: Relevance
“…It is known that ERK, as a mitogen-activated protein kinase signal transduction pathway, is modulated by the activity of CCR7 (28)(29)(30)(31)(32). The present study demonstrated that overexpression of CCR7 significantly increased the gene and protein expression levels of ERK.…”
Section: Discussionsupporting
confidence: 64%
“…It is known that ERK, as a mitogen-activated protein kinase signal transduction pathway, is modulated by the activity of CCR7 (28)(29)(30)(31)(32). The present study demonstrated that overexpression of CCR7 significantly increased the gene and protein expression levels of ERK.…”
Section: Discussionsupporting
confidence: 64%
“…294 C-C chemokine receptor 7 interacts with its ligand chemokine ligand 21 to inhibit apoptosis and induce survival and migration in CD133 + pancreatic cancer stem-like cells by increasing the expression of extracellular signal-regulated kinase 1/2 (Erk1/2) and p65. 295 Furthermore, B cell-specific Moloney murine leukemia virus integration site 1 (Bmi-1) also enhances the p65 protein in gastric CSCs. 296 MicroRNAs also play an important role in promoting the proliferation of CSCs.…”
Section: Major Signaling Pathways In Cscsmentioning
confidence: 99%
“…Activation of this receptor by CCL21 leads to the acquisition of EMT markers (Eto-N-cadherin switch, MMP9 expression) and increased invasive properties. This involves Erk/NF-jB signaling (Zhang et al, 2016c).…”
Section: Ccl21mentioning
confidence: 99%